Encapsulated Mixture of Methyl Salicylate and Tributyrin Modulates Intestinal Microbiota and Improves Growth Performance of Weaned Piglets - Yusen Wei; Jiangdi Mao; Jingliang Liu; Yu Zhang; Zhaoxi Deng; Jiaqi Lv; Maolong He; Jianxin Liu; Haifeng Wang (Microorganisms, 2021)
Tributyrin and essential oils have been used as alternatives to antimicrobials to improve gut health and growth performance in piglets. This study was to evaluate the effects of a dietary supplement with two encapsulated products containing different combinations of tributyrin with oregano or with methyl salicylate on growth performance, serum biochemical parameters related to the physiological status, intestinal microbiota and metabolites of piglets. A total of 108 weaned crossbred piglets (Yorkshire × Landrace, 21 ± 1 d, 8.21 ± 0.04 kg) were randomly divided into three groups. Piglets were fed with one of the following diets for 5 weeks: a basal diet as the control (CON); the control diet supplemented with an encapsulated mixture containing 30% of methyl salicylate and tributyrin at a dosage of 3 kg/t (CMT); and the control diet supplemented with an encapsulated mixture containing 30% of oregano oil and tributyrin at a dosage of 3 kg/t (COT). At the end of the feeding trial, six piglets from each group were slaughtered to collect blood and gut samples for physiological status and gut microbiological analysis. The study found that the CMT group was larger in feed intake (FI) (p < 0.05), average daily gain (ADG) (p = 0.09), total protein (TP), albumin (ALB), glutathione peroxidase (GSH-PX) (p < 0.05), blood total antioxidant capacity (T-AOC) (p < 0.05), and crypt depth in the ileum (p < 0.05) compared with the CON group. The genus abundance of Tissierella and Campylobacter in the CMT group was significantly decreased compared with the CON group. The CMT group also resulted in significantly higher activity in amino acid metabolism and arginine biosynthesis compared with the CON group. The COT group was larger in T-AOC, and the genus abundance of Streptophyta and Chlamydia was significantly increased in the ileum compared with the CON group. Data analysis found a significantly high correlation between the genus abundance of Chlamydia and that of Campylobacter in the ileum. The genus abundance of Campylobacter was also positively correlated with the sorbitol level. In general, the results indicated that the supplementation of both encapsulated mixtures in diet of weaned piglets could improve the animal blood antioxidant capacity. Additionally, the encapsulated mixture of methyl salicylate plus tributyrin improved the growth performance and resulted in certain corresponding changes in nutrient metabolism and in the genus abundance of ileum microbial community.